Clinical significance of programmed death‐1 and programmed death‐ligand 1 expression in the tumor microenvironment of clear cell renal cell carcinoma. Issue 6 (13th May 2019) - Mikami, Shuji; Mizuno, Ryuichi; Kondo, Tsunenori; Shinohara, Nobuo; Nonomura, Norio; Ozono, Seiichiro; Eto, Masatoshi; Tatsugami, Katsunori; Takayama, Tatsuya; Matsuyama, Hideyasu; Kishida, Takeshi; Oya, Mototsugu; et al.
Abstract: Recently, immunotherapy based on blocking immune checkpoints with programmed death‐1 (PD‐1) or PD‐ligand 1 (PD‐L1) Abs has been introduced for the treatment of advanced clear cell renal cell carcinoma (ccRCC), especially tumors resistant to vascular endothelial growth factor‐tyrosine kinase inhibitors (VEGF‐TKIs), but the significance of their expression in the tumor microenvironment is unclear. We investigated these immune checkpoint markers in tumor cells and tumor‐infiltrating immune cells (TIIC) in the tumor microenvironment of 100 untreated and 25 VEGF‐TKI‐treated primary ccRCC tissues. Upregulated expression of PD‐1 and PD‐L1 by TIIC, and PD‐L1 by tumor cells was associated with the histological grade and unfavorable prognosis of RCC patients. High PD‐1 and PD‐L1 expression by TIIC was associated with a poorer response to VEGF‐TKI, whereas PD‐L1 expression by tumor cells did not affect the efficacy of the treatment. Furthermore, increased PD‐1‐positive TIIC and PD‐L1‐positive TIIC were observed in tumors treated with VEGF‐TKIs compared with those in untreated tumors. Our data suggest that PD‐1 and PD‐L1 expression by TIIC in the tumor microenvironment is involved in treatment resistance, and that sequential therapy with immune checkpoint inhibitors could be a promising therapeutic strategy for ccRCC resistant to VEGF‐TKI treatment. Abstract : In the present study, we showed that PD‐1 and PD‐L1 expression by tumor‐infiltrating immune cells (TIIC) is associated with malignant potential and poor response to vascular endothelial growth factor‐tyrosine kinase inhibitor (VEGF‐TKI) treatment in renal cell carcinoma (RCC) patients. Moreover, RCC patients treated with VEGF‐TKI had significantly more PD‐1‐ and PD‐L1‐positive TIIC compared with untreated tumors. These results suggested that upregulated PD‐1 and PD‐L1 expression by TIIC in the tumor microenvironment is associated with resistance to VEGF‐TKI treatment, and that blocking the PD‐1/PD‐L1 pathway could be an effective sequential therapy for RCC resistant to VEGF‐TKI treatment.